2019
DOI: 10.1016/j.anaerobe.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides synthesized by Bifidobacterium animalis subsp. lactis interact with TLR4 in intestinal epithelial cells

Abstract: The toll-like receptors involved in recognition of the exopolysaccharide produced by two isogenic, ropy and non-ropy, Bifidobacterium animalis subsp. lactis strains were investigated. Both strains interact with human embryonic kidney (HEK)-293 cells via TLR2, whereas purified EPSs specifically stimulate TLR4 regardless their molar mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The study conducted with EPS obtained from isogenic Bifidobacterium animalis subsp. lactis strains represents its capability to stimulate TLR-4 regardless of their molar mass in mouse colitis model [84]. The monosaccharide galactose present in EPS of Lactobacillus reuteri Mh-001 influenced anti-inflammatory activity on the macrophages [85].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…The study conducted with EPS obtained from isogenic Bifidobacterium animalis subsp. lactis strains represents its capability to stimulate TLR-4 regardless of their molar mass in mouse colitis model [84]. The monosaccharide galactose present in EPS of Lactobacillus reuteri Mh-001 influenced anti-inflammatory activity on the macrophages [85].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…In our study the TLR signaling adaptor MyD88 was necessary to activate the NF-κB pathway by all B. breve strains tested. This was not entirely surprising considering previous studies linking bifidobacterial immunomodulation to the TLR family and MyD88 (Jeon et al, 2012;Schiavi et al, 2018;Verma et al, 2018;Castro-Bravo et al, 2019). The absence of EPS from both B. breve UCC2003 and JCM7017 drove different cytokine responses by BMDMs.…”
Section: Discussionmentioning
confidence: 70%
“…This variation could, in principle, lead to a vast number of distinct EPS structures and, theoretically to different immunomodulatory effects on the host. Reports indicate that purified EPS from two different bifidobacterial species can be detected by host innate immune PRRs – toll like receptor (TLR) 2 and TLR4 ( Schiavi et al, 2018 ; Castro-Bravo et al, 2019 ). Bifidobacterial EPS has also been shown to ameliorate inflammation in murine pulmonary and intestinal models of inflammation ( Hidalgo-Cantabrana et al, 2016 ; Schiavi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this genus, as well as in Bifidobacterium spp., heteropolysaccharides, which are those having different monosaccharides (typically D-glucose, D-galactose and L-rhamnose), are also synthesized [23]. Both EPS types constitute a protective cover for the producing bacterium, but also act as an MAMP that will be recognized by different PRRs, thus inducing different responses in the host [24]. Little is known about the PRRs involved in the recognition of EPS synthesized by probiotics.…”
Section: Exopolysaccharides and Immunomodulationmentioning
confidence: 99%
“…Little is known about the PRRs involved in the recognition of EPS synthesized by probiotics. It has been shown that specific β-glucans could act as ligands for certain C-type lectins (such as Dectin 1) located in the intestinal epithelium [25]; additionally, specific heteropolymers synthesized by bifidobacteria or lactobacilli can be recognized by TLR (toll like receptor)-4 [24,26,27].…”
Section: Exopolysaccharides and Immunomodulationmentioning
confidence: 99%